Identifying types of simultaneous fault in transmission line using discrete wavelet transform and fuzzy logic algorithm - Ngaopitakkul, Atthapol; Apisit, Chaowat; Bunjongjit, Sulee; Pothisarn, Chaichan (My University, 2013)
In the literature for fault classification, several decision algorithms have different solutions and techniques. These research works have been rarely mentioned about simultaneous faults in transmission systems. This paper presents the decision algorithm for identifying types of simultaneous fault along the transmission line. Decision algorithms based on discrete wavelet transform (DWT) and fuzzy logic are investigated. The analysis of fault signals is performed using DWT. The DWT is used in order to detect the high frequency components. The coefficient details (phase A, B, C and zero sequence of post-fault current signals) of DWT at the first peak time that positive sequence current can detect fault, are performed as an input for the fuzzy logic. The result shows that the accuracy of the proposed algorithm is highly satisfactory. © 2013 ICIC International.
Keywords: Fuzzy logic; Simultaneous fault; Transmission line; Wavelet transform